The obstacles to combat against COVID-19 pandemic and the remedies: Bangladesh scenario - Mst. Rashida Pervin; Rehana Parvin; Md. Ashraful Babu; Md. Mortuza Ahmmed; Roy Rillera Marzo (SAGE Publishing, 2021)
Background: Bangladesh has been going through the austerity of the unique COVID-19 for more than a year like several other nations in the world in spite of concerted efforts taken by the government along with other concerned authorities who have advocated compulsory guidelines involving social distancing procedures accompanied by lockdown to have control over the pandemic. In this paper, the barriers faced by the government to protect people from the COVID-19 pandemic have been investigated. Also, the number of daily infected people against the number of daily tests has been underlined to comprehend the overall pandemic picture in Bangladesh. Design and Methods: A descriptive study has been carried out to investigate the obstacles to tackle the COVID-19 pandemic for this country. The intensity of the outbreaks of the pandemic in this country is stated from March 8, 2020, to February 12, 2021. Secondary data have been employed from different sources to serve the goals of the study. Results: The poor management in the health sector of Bangladesh has been an issue of major concern during the early stage of COVID-19 which incorporates deficiency of medical equipment, lack of facilities for testing COVID-19, poor patient management, and uncertainty in the medication system. Finally, some recommendations have been proposed for the concerned organizations to tackle the current pandemic and as well in the future. Conclusions: To control this COVID-19 pandemic, it is necessary to find the difficulties and discover the remedies which have been done in this paper for the Bangladesh perspective.